Exploring the Concepts of Halal and Thayyib in the Production of Es Selendang Mayang: A Study on Islamic Education in Tangerang City - Destiani Rahmawati; Dewi Tri Komalasari; Farhan Kamiluloh; Robiah Robiah (Lembaga Yasin AlSys, 2026)
Amid the rapid growth of the global halal food market and its emphasis on business ethics, this study analyzes the role of Islamic religious education in shaping the professional attitude and honesty of Es Selendang Mayang artisanal business actors in Tangerang, with a particular focus on how religious values are applied in traditional small business practices. Using a qualitative approach based on interviews, observations, and questionnaires, the study employs thematic analysis to interpret the resulting qualitative data. The findings indicate an increased awareness of honest and professional conduct that supports the sustainability of halal products, with Islamic religious education functioning as a key source of motivation and moral guidance in facing business challenges. Furthermore, the implementation of religious learning technology is shown to be effective in expanding access to religious education and accelerating positive behavioral change among business actors. The study concludes that sustained coaching programs that integrate local religious and cultural values can serve as a strategic model for empowering traditional businesses, thereby strengthening ethical practices and the long-term viability of halal food enterprises.